The Josefina story quilt - Coerr, Eleanor; Degen, Bruce; Bobby, Ann. (New York : HarperCollins, 1995)
While traveling west with her family in 1850, a young girl makes a patchwork quilt chronicling the experiences of the journey and reserves a special patch for her pet hen Josefina.
Book illustrations by Bruce Degen.
Side 1 has page turn signals ; side 2 has uninterrupted reading.
Performed by Ann Bobby.
Keywords: Quilting -- Juvenile fiction -- Sound recordings; Chickens -- Juvenile fiction -- Sound recordings; Overland journeys to the Pacific -- Juvenile fiction -- Sound recordings